2009
DOI: 10.1080/09640560903181220
|View full text |Cite
|
Sign up to set email alerts
|

Convergence or divergence in desertification risk? Scale-based assessment and policy implications in a Mediterranean country

Abstract: This paper explores changes (1990-2000) in two environmental indexes with the aim of providing empirical evidence on regional and local convergence in an increasing-impact phenomenon such as Land Degradation (LD) in Italy. Convergence analysis for ESAI (Environmental Sensitive Area Index) and LVI (Land Vulnerability Index) was developed at five different geographical scales. Results indicate that territorial disparities in land vulnerability tend to increase during the investigated period following a defined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 58 publications
1
11
1
1
Order By: Relevance
“…This observation is in line with the results illustrated in previous studies which classify some areas of northern Italy as exposed to the desertification risk as many southern areas (e.g. Salvati and Zitti 2009c). This analysis was applied separately to the same indicators calculated for three geographical belts: northern, central and southern Italy.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This observation is in line with the results illustrated in previous studies which classify some areas of northern Italy as exposed to the desertification risk as many southern areas (e.g. Salvati and Zitti 2009c). This analysis was applied separately to the same indicators calculated for three geographical belts: northern, central and southern Italy.…”
Section: Resultssupporting
confidence: 67%
“…It was found that the economic determinants of LD act differently in northern and southern Italy according to the contrasting development paths that have characterised the two areas during the last 50 years at least (Salvati and Zitti 2008b). Together with the economic weaknesses of southern Italy due to the 'development deficit' which is shared with other Mediterranean areas (King et al 2001), the present study shows evidence of an 'environmental divide' between northern-central Italy and southerninsular Italy, as the latter region shows, on average, a persistent increase in land surface vulnerable to degradation which is not comparable to that observed in the former area (Salvati and Zitti 2009c). The reasons why southern Italy remains one of the most disadvantaged regions in the European Union are extremely complex as they depend on path-dependent economic factors that are difficult to reverse (e.g.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…Candidate responses to LD can be classified as 'broad' or 'narrow' spectrum based on the observed correlation with the local background and the overall level of desertification risk (e.g. Salvati and Zitti, 2009). Fire prevention, sustainable farming and protected areas were identified as broad-spectrum actions (Kosmas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary approach based on biophysical and socioeconomic factors is required to identify areas vulnerable to desertification. Several mathematical models have been developed across the world to delineate areas vulnerable to desertification (Dasgupta, Sastry, Dhinwa, Rathore, & Nathawat, ; Salvati & Zitti, ; Symeonakis, Karathanasis, Koukoulas, & Panagopoulos, ). The Environmental Sensitivity Index is assessed by computing the Soil Quality Index, Climate Quality Index, Vegetation Quality Index, and Management Quality Index in the MEDALUS methodology (Kosmas, Ferrara, Briasouli, & Imeson, ).…”
Section: Introductionmentioning
confidence: 99%